Structure-based ligand discovery: elaborating fragment hits in silico - Leung, SH (2019)
The high attrition rates of drug discovery have been a key motivation for the development of computational methods to design better, safer, more promising molecules. Hit-to-lead development is often driven by the subjective decisions of medicinal chemists. There is growing interest in developing more objective tools to explore the vastness of chemical space. Fragment-based drug discovery offers the advantage of a high coverage of chemical space through the identification of fragment hits, which are typically more weakly binding and smaller than drug-like molecules. The process of fragment elaboration aims to increase their potency and potentially other objectives. However, currently there is no agreed best method for how to elaborate fragment hits using all structural information acquired.